SU(3) Symmetry Breaking Decays of Charmonia: SU(3) symmetry - Saeed, Khadija; Amin, Aneela; Younas, Farzana; Khalid, Amir; Saeed, Muhammad Qamar; Islam, Ghalib ul (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
SU (3) symmetry breaking in several Charmonia decays was studied using the data from world’s leading High Energy Physics laboratories. The charm factory BESIII was the main source of information. Branching fraction with different number of events of J/ψ, ψ (2S) → ɅɅ̅, ΣΣ̅, Ξ Ξ were computed. The total number of events for J/ψ from 1.32 × 106 to 1310.6 × 106 and that of ψ (2S) from 3.96 × 10106 to 448.1× 10106 were studied. The corresponding branching fractions and value of decay constant α for above mentioned channels became more precise with increase of the number of events. The results of their comparison have been elaborated and are compiled in tabular form. All the data is collected year wise from the date of arise of this phenomenon (1984) to present. It has been observed from the study that with the passage of time and increased number of events gives more precise values of branching fraction and decay constant α.